WILLIAM SHAKESPEARE’S LEGACY IN 21 CENTURY - Mirzakhanova Sabina Khamidulla qizi; Khamitov Eldorbek Erkin og’li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
William Shakespeare was a renowned English poet, playwright.William Shakespeare has had an incredible influence on not just English literature, but the English language in general. Also known as "the Bard of Avon," he is the author of many of the plays that most students in English-speaking countries study in school. Even people who have not read his works know some of Shakespeare's most famous lines. In this article, we'll explain W. Shakespeare's life, the appeal of Shakespeare, the most famous playwrights in English history, and his impact on the English language.